Achieving sustainability in global sourcing: towards a conceptual framework. Issue 1 (7th October 2019) - Jiang, Yan; Jia, Fu; Blome, Constantin; Chen, Lujie
Abstract : Purpose: This paper aims to set out the development, based on the extant literature, an integrated conceptual framework for the emergent field of sustainable global sourcing (GS) that synthesizes its antecedents, GS practices and sustainable performance. Design/methodology/approach: Conceptual theory building combined with content analysis is used to develop a framework and propositions representing a middle-range theory of sustainable GS. A literature review of the 89 most influential papers is followed by a further discussion based on the resource orchestration perspective (ROP) to advance an integrated conceptual framework. Findings: Three main themes are identified from the literature as antecedents, GS practices and sustainable performance, with each theme being detailed in a variety of constructs. Based on the ROP, the relationships between these constructs are revealed, and therefore, an integrated conceptual framework is advanced via three sets of propositions in recourse orchestration breadth, recourse orchestration depth and resource orchestration evolution, respectively. Eight directions for future research are further proposed. Originality/value: First, this study provides a comprehensive framework for future study in the emergent field of sustainable GS. Second, the authors contribute to theory development by proposing a ROP to explore the GS practices towards sustainability. Third, the future research directions we proposed can benefit scholars interested in the overlapping areas of GS and sustainability.